Cerium oxide nanozyme modulate the 'exercise' redox biology of skeletal muscle. (16th May 2017) - Arya, Aditya; Sethy, Niroj Kumar; Gangwar, Anamika; Bhargava, Neelima; Dubey, Amarish; Roy, Manas; Srivastava, Gaurav; Singh, Sushil Kumar; Das, Mainak; Bhargava, Kalpana
Abstract: 'Exercise' is a double-edged sword for the skeletal muscle. Small amount of ROS generated during mild exercise, is essential for normal force generation; whereas large quantity of ROS generated during intense exercise, may cause contractile dysfunction, resulting in muscle weakness and fatigue. One of the key question in skeletal muscle physiology is 'could antioxidant therapy improve the skeletal muscle endurance? A question, which has resulted in contradictory experimental findings till this date. This work has addressed this 'very question' using a synthetic, inorganic, antioxidant nano-material viz., 'cerium oxide nanozyme' (CON). It has been introduced in the rat by intramuscular injection, and the skeletal muscle endurance has been evaluated. Intramuscular injections of CON, concurrent with exercise, enhanced muscle mass, glycogen and ATP content, type I fiber ratio, thus resulting in significantly higher muscle endurance. Electron microscope studies confirmed the presence of CON in the vicinity of muscle mitochondria. There was an increase in the number and size of the muscle mitochondria in the CON treated muscle, following exercise, as compared to the untreated group with only exercised muscle. Quantitative proteomics data and subsequent biological network analysis studies, identified higher levels of oxidative phosphorylation, TCA cycle output and glycolysis in CON supplemented exercised muscle over only exercised muscle. This was further associated with significant increase in the mitochondrial respiratory capacity and muscle contraction, primarily due to higher levels of electron transport chain proteins like NDUFA9, SDHA, ATP5B and ATP5D, which were validated by real-time PCR and western blotting. Along with this, persistence of CON in muscle was evaluated with ICP-MS analysis, which revealed clearance of the particles after 90 d, without exhibiting any inflammation or adverse affects on the health of the experimental animals. Thus a higher physiological endurance of the CON supplemented exercised muscle' opens new avenues in skeletal muscle therapeutic, space and sports medicine.